First record of a living species of the genus Janulum (Class Demospongiae) in the Southern Hemisphere - Kelly, Michelle; Erpenbeck, Dirk; Morrow, Christine; Soest, Rob Van (Zootaxa, 2015)
A new species of the enigmatic sponge genus Janulum de Laubenfels, 1936 was discovered recently on the Louisville Seamount Chain, in International Waters to the east of New Zealand; two small specimens were found encrusting the interstices of the stony coral Solenosmilia variabilis Duncan at a depth of 1200–1600 m. Janulum imago sp. nov., is described and compared with the genus type J. spinispiculum (Carter, 1876) from the North Atlantic. Janulum was also recorded from the Late Eocene Oamaru Diatomite of southern New Zealand in 1892, but was misidentified as genus Plocamia Schmidt (Order Poecilosclerida Topsent, Family Microcionidae Carter). Fossil species Janulum princeps sp. nov. is also described herein and represents the first record of this North Atlantic-Arctic Ocean genus in the Southern Hemisphere. The validity of J. filholi (Topsent, 1890), the second and only other North Atlantic species currently assigned to Janulum, is considered in the context of J. spinispiculum and the new species J. imago sp. nov.